The Development of e-Book Based on Problem and Project Based Learning Assisted by Book Creators - Dewi Zakiyatus Sholihah; Naniek Sulistya Wardani; Aris Kukuh Prasetyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
The aim of this research is; 1) develop an initial e-book assisted PPjBL approach platform Book Creator for fourth grade elementary school students; 2) describes the initial draft form of teaching materials in the form of an e-book based on the PPjBL approach assisted by a platform Book Creator for fourth grade elementary school students. This research is a kind of research and development or R&D (Research & Development). This study uses the Sukmadinata modification research stage which consists of 3 stages, such as; preliminary study (stage 1) consists of library research activities, field observations, and preparation of an initial draft; development (stage 2) consists of the product preparation stage, design validation, improvement, product testing, product improvement and determination; and product testing and socialization (stage 3). Data was collected using test and non-test techniques in the form of observation. This study uses qualitative data analysis techniques. Based on the results of the study, it was concluded that the e-book developed was